Inflation-income inequality nexus in South Africa: The role of inflationary environment - Eliphas Ndou (Journal of Applied Economics, 2024)
We estimate vector autoregressive models to examine the effect of the 3 to 6 per cent inflation target band in the inflation and income inequality nexus in South Africa. We use quarterly data spanning 1993Q1 to 2016Q3 to analyse how growth in income inequality responds to positive inflation shocks when inflation is within the 3 to 6 per cent target band versus when it exceeds 6 per cent. Evidence indicates that positive inflation shocks within the 3 to 6 per cent inflation target band lead to an insignificant decline in income inequality. However, greater income inequality results when inflation exceeds 6 per cent threshold. This suggests that the inflation-income inequality nexus in South Africa is nonlinear due to the 3 to 6 per cent inflation target range. Thus, inflation above 6 per cent is harmful as it increases income inequality. Policymakers should pursue policies that maintain the existing target band.
Keywords: D33; E58; E61; 330; ID31; income distribution; Income equality; inflation; monetary policy